Artifacts and allegiances: How museums put the nation and the world on display - Levitt, Peggy (Oakland University of California Press, 2015)
What can we learn about nationalism by looking at a country's cultural institutions? How do the history and culture of particular cities help explain how museums represent diversity? Artifacts and Allegiances takes us around the world to tell the compelling story of how museums today are making sense of immigration and globalization. Based on firsthand conversations with museum directors, curators, and policymakers; descriptions of current and future exhibitions; and the inside stories about the famous paintings and iconic objects that define collections across the globe, this work provides a close-up view of how different kinds of institutions balance nationalism and cosmpolitanism. By comparing museums in Europe, the United States, Asia, and the Middle East, Peggy Levitt offers a fresh perspective on the role of the museum in shaping citizens. Taken together, these accounts tell the fascinating story of a sea change underway in the museum world at large
Keywords: Museums--Social aspects; Museums and community; Diversity